2010
DOI: 10.1111/j.1447-0756.2010.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine, folic acid and vitamin B12 levels in maternal and umbilical cord plasma and homocysteine levels in placenta in pregnant women with pre-eclampsia

Abstract: Maternal and fetal serum homocysteine levels were found to be significantly higher in severe pre-eclampsia group compared to mild pre-eclampsia and control groups suggesting that elevated serum levels of homocysteine might be associated with severity of pre-eclampsia. On the other hand it seems like elevated serum homocysteine levels were not associated with deficiency of folic acid and vitamin B12.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 21 publications
7
36
1
1
Order By: Relevance
“…The authors conclude that the levels of homocysteine are significantly higher in the group of women with severe preeclampsia as compared with the groups of women with mild preeclampsia and those with normal pregnancy, suggesting that the increased homocysteine levels may be associated with the severity of preeclampsia. They also consider that elevated homocysteine levels do not appear to be accompanied by folic acid and vitamin B12 deficiency (24). A similar homocysteine pattern was also observed in our study.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The authors conclude that the levels of homocysteine are significantly higher in the group of women with severe preeclampsia as compared with the groups of women with mild preeclampsia and those with normal pregnancy, suggesting that the increased homocysteine levels may be associated with the severity of preeclampsia. They also consider that elevated homocysteine levels do not appear to be accompanied by folic acid and vitamin B12 deficiency (24). A similar homocysteine pattern was also observed in our study.…”
Section: Discussionsupporting
confidence: 77%
“…absence of biological plausibility; therefore, they consider that the association of hyperhomocysteinemia and preeclampsia cannot be explained by the current literature data (23). In contrast to the study by Mignini et al (23), a more recent report by Acilmis et al (24) offers an explanation of the obscurities related to hyperhomocysteinemia and pregnancy by differentiating severe and mild preeclampsia. They monitored the levels of homocysteine, folic acid and vitamin B12 in three groups of pregnant women, i.e.…”
Section: Discussioncontrasting
confidence: 50%
“…Blood concentrations of homocysteine are determined by various dietary factors, including folic acid and vitamin B 12 , by alteration in physiology, such as renal impairment, and by variation in the activity of enzymes in the various pathways as a result of genetic polymorphisms, some of which are commonly found in the population. Hyperhomocysteinemia has been associated with vascular disease, although whether it is cause or effect is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…11 Acilmis et al concluded that maternal and fetal serum homocysteine levels were found to be significantly higher in severe pre-eclampsia group compared to mild pre-eclampsia and control groups suggesting that elevated serum levels of homocysteine might be associated with severity of pre-eclampsia. 12 It has been hypothesized that in vitro, homocysteine enhances spontaneous contractions of myometrium. Applying the same it has been postulated that high homocysteine in early pregnancy leads to preterm labour.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in several studies, women with preeclampsia had significantly higher homocysteine concentrations than normotensive pregnant women; however, no significant differences were found in serum or plasma vitamin B-12 concentrations between groups (86-88). Among patients with severe preeclampsia in Greece (blood pressure: $170/110 mm Hg) and Turkey (blood pressure: $160/110 mm Hg), only homocysteine concentrations were significantly higher, compared with normotensive pregnant women (P < 0.001 and P < 0.05, respectively) (86,87). In addition, in a cohort Gestational diabetes.…”
Section: Literature Reviewmentioning
confidence: 99%